PENGARUH AKUNTABILITAS, TRANSPARANSI, PARTISIPASI MASYARAKAT TERHADAP PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN DANA DESA PADA DESA SONGAN B KECAMATAN KINTAMANI KABUPATEN BANGLI - Ade Ayu Anggreni Putri; I Wayan Sudiana; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2021)
Village funds are the source of income for each village, need to be controlled over their management, it should right on target and can improve people's lives. This study aims to determine the effects of Accountability, Transparency, Community Participation on Community Empowerment in Village Fund Management in Songan B Village, Kintamani District, Bangli Regency. The population in this study were the people of Songan B Village, Kintamani District, Bangli Regency who had voting rights and / or were 17 years old, while 100 people were the object of research (sample). The sampling technique used was purposive sampling technique. The results showed that the variables of transparency and community participation had a positive and significant effect on community empowerment, while the accountability variable had no effect on community empowerment.